Pengaruh Gadget terhadap Motivasi Berolahraga Siswa SMAN 1 Jombang - Khairunisa Salsabilah Putri; Yudi Dwi Saputra; Hijrin Fithroni; Abdul Aziz Hakim (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Rapid advancements in digital technology have significantly transformed the behavioral patterns of adolescents, including their participation in physical activities. Heavy reliance on gadgets is frequently linked to increased sedentary tendencies and reduced physical engagement. This study aims to examine the influence of gadget use on students' motivation to exercise at SMAN 1 Jombang. A quantitative correlational design was employed, with a total population of 900 students and a sample of 90 respondents selected through random sampling. The research instruments included questionnaires on gadget use and exercise motivation, which were developed based on relevant indicators and adapted from previous studies. Data were analyzed using descriptive analysis and simple linear regression with the assistance of SPSS version 27.01 IBM for Windows. The results showed that gadget use has an effect on students’ motivation to exercise, with a coefficient of determination (R-Square) of 0.053. This indicates that gadget use contributes relatively little to exercise motivation. The findings suggest that the influence of gadget use on exercise motivation is not direct but is influenced by the pattern and purpose of its use. Gadget use dominated by passive entertainment activities, such as social media and video streaming, tends to be associated with increased sedentary behavior. In contrast, productive use has the potential to positively influence exercise motivation. In addition, exercise motivation is also influenced by intrinsic and extrinsic factors, such as interest, health awareness, school environment, and social support. Therefore, efforts to improve exercise motivation should not only focus on limiting gadget use but also on promoting wise usage management and strengthening students’ physical activity habits. The advancement of digital technology has influenced adolescents’ activity patterns, including their participation in sports. High levels of gadget use are often associated with increased sedentary behavior and reduced physical activity. This study aims to examine the effect of gadget use on students’ motivation to exercise at SMAN 1 Jombang. This research employed a quantitative approach with a correlational research design. The population consisted of 900 students, and the sample was determined using random sampling, resulting in 90 respondents. The research instruments were questionnaires on gadget use and exercise motivation, developed based on relevant indicators and adapted from previous studies. The data were analyzed using descriptive analysis and simple linear regression with the assistance of SPSS version 27.01 IBM for Windows. The results of the study indicate that gadget use has an effect on students’ motivation to exercise, with a regression value of 0.053. The research results show that gadget use has an influence on students’ motivation to exercise, with a regression value of 0.053. This value indicates that gadget use has a relatively small contribution to students’ motivation to exercise. Thus, gadget use does not always have a negative impact on exercise motivation. When used properly, gadgets can also support students’ motivation to remain active and participate in physical activity.